Contribution of the USSR State Committee on Science and Technology to development of agricultural science - A. V. Rychkov (Омский научный вестник: Серия "Общество. История. Современность")
The publication analyzes the main directions of the scientific and organizational activities of the USSR State Committee on Science and Technology (SCST of the USSR) to improve the organization of agricultural research. The SCST of the USSR studied the possibilities of using the latest scientific achievements in production, oriented agricultural scientists to the formation of comprehensive recommendations for agriculture, and organized a search for new innovative forms. The author comes to the conclusion that the activity of the SCST of the USSR outlined the direction of the processes of research and production integration in agriculture in the last Soviet decades